Enriching the content of extracurricular activities in universities with the ideas of interactive learning - Бєкірова, Л. Є. (Educational Dimension, 2021)
The author reveals the problem of forming a willingess to primary school teachers to use interactive learning technologies and enrich extracurricular work in high school ideas of interactive learning.